Strategic Management of the School Principal in Enhancing Academic Competitiveness at SD Al-Qur’an Ummul Quro Pamekasan - Amaliyatus Shofiyah; Moh Muslim; Kukuh Santoso (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2025)
This study examined the strategies of the school principal in enhancing competitiveness at SD Al-Qur’an Ummul Quro Pamekasan, with the aim of achieving successful implementation and application of strategies that directly impacted the strengthening of public trust and the improvement of student quality, This study tries to describe in detail the school principal’s strategies at the operational level, encompassing the stages of formulation, implementation, and evaluation, which were specifically designed to respond to challenges related to geographical conditions and local inter-school competition in rural areas, by integrating the general and religious curriculum within the context of school strategic management. This study used a descriptive qualitative approach using observation, interviews, and documentation methods. The data analysis was conducted using the Miles and Huberman model through the processes of data collection, data reduction, data display, and conclusion drawing. The results of the study showed that the implementation of integrated strategies had a positive impact on the increase in student enrollment, students’ academic achievement, and public trust. The school successfully established a competitive advantage based on Qur’anic values, which served as a distinctive feature compared to other schools